2018
DOI: 10.1111/bjc.12214
|View full text |Cite
|
Sign up to set email alerts
|

Reduced fear‐of‐self is associated with improvement in concerns related to repugnant obsessions in obsessive–compulsive disorder

Abstract: Objective. The potential causal and maintaining role of vulnerable self-themes and beliefs about the self in obsessive-compulsive disorder (OCD) have received increasing attention from cognitive-behavioural theorists. This interest was translated into the development of a self-report measurement of the feared self (the fear of who one might be or become), a construct theoretically and empirically pertinent to unwanted thoughts and impulses in OCD (i.e., repugnant obsessions).Method. The current study aimed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 41 publications
2
27
0
Order By: Relevance
“…In summary, there is strong evidence that both fear of self and self-ambivalence are significant predictors of OCD symptomatology in general. This was a consistent finding across all but one (Aardema et al, 2018) of the studies included for review. This study looked at change in symptoms before and after treatment.…”
Section: Discussionsupporting
confidence: 74%
See 4 more Smart Citations
“…In summary, there is strong evidence that both fear of self and self-ambivalence are significant predictors of OCD symptomatology in general. This was a consistent finding across all but one (Aardema et al, 2018) of the studies included for review. This study looked at change in symptoms before and after treatment.…”
Section: Discussionsupporting
confidence: 74%
“…The evidence supporting the ability of self-ambivalence to predict obsessional thoughts was more varied. Of the two papers investigating this, one paper showed a strong significant predictive effect (Aardema et al, 2013) and another, by the same first author (Aardema et al, 2018) As the MA subscale of the SAM was found to be a significant predictor of importance of thoughts and responsibility, but not contamination , it would be interesting for future research to assess the extent to which this concept could predict mental contamination, as opposed to the physical contamination fears that are perhaps better represented by the VOCI subscale. The contamination subscale on the VOCI has items such as "I am excessively concerned about germs or disease" and "I feel very contaminated if I touch an animal," which may be less relevant to those people who experience mental contamination.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations